Sprite produced by consecutive impulse charge transfers following a negative stroke: Observation and simulation. Issue 8 (22nd April 2016) - Lu, Gaopeng; Cummer, Steven A.; Tian, Ye; Zhang, Hongbo; Lyu, Fanchao; Wang, Tao; Stanley, Mark A.; Yang, Jing; Lyons, Walter A.
Abstract: On the morning of 5 June 2013, two cameras of the SpriteCam network concurrently captured a red sprite with diffuse halo over a mesoscale convective system (MCS) passing the panhandle area of Oklahoma. This sprite was produced by a negative cloud‐to‐ground (CG) stroke with peak current of −103 kA in a manner different from previous observations in several aspects. First of all, the causative stroke of sprite is located by the National Lightning Detection Network (NLDN) in the trailing stratiform of MCS, instead of the deep convection typically for negative sprites. Second, the sprite‐producing stroke was likely the first stroke of a multistroke negative CG flash (with ≥6 CG strokes) whose evolution was mainly confined in the lower part of thunderstorm; although the parent flash of sprite might contain relatively long in‐cloud evolution prior to the first stroke, there is no evidence that the negative leader had propagated into the upper positive region of thundercloud as typically observed for the sprite‐producing/class negative CG strokes. Third, as shown by the simulation with a two‐dimensional full‐wave electrodynamic model, although the impulse charge moment change (−190 C km) produced by the main stroke was not sufficient to induce conventional breakdown in the mesosphere, a second impulse charge transfer occurred with ~2 ms delay to cause a substantial charge transfer (−290 C km) so that the overall charge moment change (−480 C km) exceeded the threshold for sprite production; this is a scenario different from the typical case discussed by Li et al. (2012). As for the source of the second current pulse that played a critical role to produce the sprite, it could be an M component whose charge source was at least 9 km horizontally displaced from the main stroke or a negative CG stroke (with weak peak current for the return stroke) that was not detected by the NLDN. Key Points: Sprite produced by negative charge transfer with subcritical iCMC Sprite production by the first stroke of a multistroke negative CG flash A new mechanism for sprite production by negative CG strokes